PENERAPAN BIAYA KUALITAS DALAM MENINGKATKAN MUTU PRODUK (STUDI KASUS PT PERKEBUNAN NUSANTARA I PKS TANJUNG SEUMANTOH) - Larasanti, Dwi Fajerin; Afrianandra, Cut (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The research objective was to see how the calculation and application of quality costs in improving product quality. The population in this study PKS Tanjung Seuamantoh. This study uses primary data and secondary data by collecting data based on the PKS cost management report. The analysis technique used is descriptive qualitative analysis. The results showed that the quality costs budgeted by the company only consisted of prevention costs and appraisal costs where the realization quality costs and the budget had a difference of 15% to the realized costs, the highest percentage of quality costs was the prevention costs where realization was 92.2% and This budget of 93.3% indicates that the company prevents the occurrence of a bad product before it is detected in the hands of consumers, this shows that the inspection carried out by the company is very strict and is followed by an assessment fee where the realization is 7.8% and is budgeted at 6.7 % of this cost is not too focused because the product produced is in the form of CPO where the quality is determined at the beginning of the production process.